Current approach to diagnosing and treating necrotizing fasciitis - Łukasz Ciulkiewicz; Paulina Kryszpin; Piotr Jachimowski; Maciej Pełka; Anna Kania; Justyna Fijałkowska (Kazimierz Wielki University, 2024)
Introduction: Necrotizing fasciitis is an infrequent yet highly fatal bacterial infection characterized by widespread necrosis of fascia and subcutaneous fat tissue. Though initial symptoms resemble typical infection, necrotizing fasciitis progresses rapidly triggering acute phase response. Individuals with advanced age, chronically ill, immunocompromised, or abusing alcohol are especially susceptible to developing necrotizing fasciitis. In order to reduce mortality, early diagnosis and appropriate treatment are indispensable. Aim of the Study: Aim of this study is through evaluating existing literature to outline the contemporary diagnostic strategies and emerging therapy options for necrotizing fasciitis. Description of the State of Knowledge: Primary diagnostic methods involve clinical evaluation and surgical exploration, complemented by fresh frozen sections for rapid diagnosis and the finger test. Diagnostic imaging incorporates the use of magnetic resonance imaging, computed tomography and ultrasound. The treatment is mostly centered around surgical debridement and antibiotic therapy. Therapies that display potential efficacy include low-dose radiotherapy, hyperbaric oxygen therapy, and the use of intact fish skin grafts for tissue reconstruction after successful treatment. The emerging approach includes therapy targeting systemic inflammatory response syndrome, sepsis induced coagulopathy and critical illness related corticosteroid insufficiency.  Conclusions: The management of necrotizing fasciitis primarily depends on traditional methods. Fast identification and proper treatment are pivotal in reducing the mortality rate. Recognizing the significance of addressing the acute phase response in necrotizing fasciitis treatment introduces new possibilities for therapeutic interventions. Further research is vital to evaluate the existing approaches to necrotizing fasciitis management and explore new diagnoistic and therapeutic alternatives.